The (Un)Sustainability of Nephrology - Ivo Laranjinha; Margarida Gonçalves; Mark Harber (Publicações Ciência e Vida, 2023)
The rising prevalence of patients living with kidney disease and the recognition of the huge environmental impact of kidney care (mainly dialysis treatments) points to the unsustainability of nephrology in the near future, which has forced the nephrology field to define its sustainability as a priority for this century. In order to face this issue, nephrologists need to recognize the dimension of the environmental footprint of their activities and what topics are associated with a bigger carbon footprint or resource consumption. Nephrologists should be in the center and the driving force for the changes needed.